A new species of Mongolodectes (Orthoptera: Tettigoniidae) from Alashan Plateau in China - Liu, Chun-Xiang; Xu, Wen-Jing; Zhang, Chun-Tian (Zootaxa, 2015)
The genus Mongolodectes is endemic to vast Mongolian Plateau and has two recorded species in the Mongolian People’s Republic and one species in China’s Inner Mongolia. Here we describe one new species Mongolodectes huangi sp. n. from China’s Inner Mongolia. Further investigations are needed for precise identification and complete understanding on the fauna of the Mongolian Plateau.